Size of Company, Return on Assets, and Leverage on Tax Avoidance - Fiesty Utami; Adih Supriadi (J-MAS (Jurnal Manajemen dan Sains), 2023)
Many companies do tax avoidance in order to decrease the tax burden. Tax avoidance can be done in various ways. This research is to discover the impact of return on assets, firm size, and firm leverage on tax avoidance, partially and simultaneously. The author uses data collection methods by utilizing secondary data from the oil and gas companies’ financial statements which can be downloaded on the website. The research data was processed using analysis of multiple regression, and Eviews. This research reveals that simultaneously firm size, return on assets, and leverage have a significant and positive effect on tax avoidance. This research also shows that the company's leverage significantly gives an effect on tax avoidance activities. It means that the higher the leverage of a firm, it will affect the company's ability to avoid its taxes. Meanwhile, firm size and return on assets partially gives no effect on tax avoidance activities.